2020
DOI: 10.3389/fped.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on the Relevance of Paracetamol for Procedural Pain Management in Neonates

Abstract: Effective and safe pain relief in neonates matters. This is not only because of ethical constraints or human empathy, but even more because pain treatment is an important and crucial part of contemporary medical, paramedical, and nursing care to improve the outcome in neonatal intensive care graduates. Paracetamol (acetaminophen) is likely one of the pharmacological tools to attain this, with data on prescription practices suggesting that paracetamol is somehow the "rising star" in neonatal pain management. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
(139 reference statements)
0
17
0
Order By: Relevance
“…In vivo, in vitro and ex vivo studies have shown that APAP directly perturbs hormone-dependent processes, including inhibition of androgen production and increased oestrogen production, disruption of steroidogenesis, depletion of sulfated sex hormones, perturbation of immune function, induction of oxidative stress and indirect activation of the endocannabinoid system 1,2,[61][62][63][64][65] . Independently of APAP, these processes have been implicated as mechanisms related to the development of neurodevelopmental [66][67][68][69][70][71][72][73][74][75][76] and reproductive disorders 2 . In addition to potential effects on neuronal and reproductive development, a combination of clinical studies together with experimental work in animal models and cell lines has also suggested that APAP exposure during pregnancy might decrease fetal haematopoietic stem cell numbers alter steroidogenesis in the placenta and induce placental damage 65,[77][78][79][80] .…”
Section: Nature Reviews | Endocrinologymentioning
confidence: 99%
“…In vivo, in vitro and ex vivo studies have shown that APAP directly perturbs hormone-dependent processes, including inhibition of androgen production and increased oestrogen production, disruption of steroidogenesis, depletion of sulfated sex hormones, perturbation of immune function, induction of oxidative stress and indirect activation of the endocannabinoid system 1,2,[61][62][63][64][65] . Independently of APAP, these processes have been implicated as mechanisms related to the development of neurodevelopmental [66][67][68][69][70][71][72][73][74][75][76] and reproductive disorders 2 . In addition to potential effects on neuronal and reproductive development, a combination of clinical studies together with experimental work in animal models and cell lines has also suggested that APAP exposure during pregnancy might decrease fetal haematopoietic stem cell numbers alter steroidogenesis in the placenta and induce placental damage 65,[77][78][79][80] .…”
Section: Nature Reviews | Endocrinologymentioning
confidence: 99%
“…The rising use of paracetamol as adjunct to opioids following major surgeries between the two timepoints of our study also supports the findings of other relevant publications. A recent meta-analysis and a review showed that existing data are not sufficient to support a role of paracetamol in reducing the procedural pain in neonates but may reduce the need for morphine following major surgery (36,37).…”
Section: Changes In Medications Usedmentioning
confidence: 99%
“…Paracetamol and ibuprofen have equal efficacy for the treatment of fever in infants [24], and paracetamol has evolved into a cornerstone of effective pain relief in neonates. Paracetamol allows for reduced dosing of opioids and may be used to effectively treat moderate pain after surgery, while there is insufficient evidence to support its use for painful procedures [68,69]. Paracetamol given after assisted vaginal birth may even increase the response to subsequent painful procedures [70].…”
Section: Postnatal Use Of Paracetamol In Term and Preterm Newborn Infantsmentioning
confidence: 99%